Effects of preparatory and action planning instructions on situation-specific and general fruit and snack intake. (1st January 2017) - de Bruijn, Gert-Jan; Nguyen, Minh Hao; Rhodes, Ryan E.; van Osch, Liesbeth
Abstract: Evidence to date suggests heterogeneity in the effects of implementation intentions on health behaviour, including diet. Additional variables and study designs may impact on their effectiveness. Preparatory action, such as making sure fruits are available for consumption, may be an important additional variable. Likewise, most implementation intention research has focused on changes in general intake, yet implementation intention instructions typically require participants to consider behaviour in specific situations. Little is known on how implementation intentions impact situation-specific intake. The present study sought to add to the evidence base by comparing (1) the effects of action planning instructions versus preparatory planning instructions on (2) both situation-specific (as formulated in the implementation intention instruction) and general intake of fruits and in-between meal snack intake frequency. Fruit intake was assessed in average pieces per day, whereas snacking intake was assessed as average frequency in days per week. Using non-probability sampling, 243 undergraduate students who intended to have a healthy diet were randomized to either a standard information control condition, an action planning condition, or a preparatory planning condition. Planning manipulations were based on previous work. Two weeks later, general and situation-specific intake was assessed again in 181 participants. Data were analysed using 2 (time) x 3 (conditions) analyses of variance. Results showed that both planning manipulations were successful in decreasing snack intake frequency in the specified situation, with larger effect sizes for the action planning condition than for the preparatory planning condition. No effects were found on general snack intake frequency or fruit intake. Future planning interventions should more explicitly compare changes in situational and general intake, as well as simultaneously assessed decreases in unhealthy intake and increases in healthy intake.